1998
DOI: 10.1111/j.1574-6968.1998.tb13104.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the mineralization of [U-14C]benzene in spent mushroom substrate

Abstract: The degradation of benzene in pasteurized spent mushroom substrate (SMS) was assessed. Following a 3 month enrichment in the presence of a variety of BTEX compounds, the extent of [U‐14C]benzene mineralization in the pasteurized SMS increased with increasing incubation temperature (18°C<37°C<50°C). The concentration as well as the chemical composition used to enrich the compost's degradative activity was also shown to be involved in determining the extent of benzene mineralization. SMS induced on a 12.5 mM BTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Several works have evaluated the use of SMS as a biological source that contains white-rot fungi, nutrients and enzymes for biodegrading and mineralizing different pesticides, such as heptachlor and its metabolite heptachlor epoxide [ 62 ], DDT [ 63 ], tricyclazole [ 64 ], benzene [ 71 ], and polycyclic organic hydrocarbons (PAH) [ 65 , 66 , 67 , 71 , 72 , 73 , 74 , 75 ]. Different studies have addressed the application of SMS to bioremediate contaminated soils by organic compounds including pesticides [ 62 , 64 , 68 , 69 ] or PAH [ 65 ] ( Table 5 ).…”
Section: Application Of Sms To Soils and Its Effect On The Behaviomentioning
confidence: 99%
“…Several works have evaluated the use of SMS as a biological source that contains white-rot fungi, nutrients and enzymes for biodegrading and mineralizing different pesticides, such as heptachlor and its metabolite heptachlor epoxide [ 62 ], DDT [ 63 ], tricyclazole [ 64 ], benzene [ 71 ], and polycyclic organic hydrocarbons (PAH) [ 65 , 66 , 67 , 71 , 72 , 73 , 74 , 75 ]. Different studies have addressed the application of SMS to bioremediate contaminated soils by organic compounds including pesticides [ 62 , 64 , 68 , 69 ] or PAH [ 65 ] ( Table 5 ).…”
Section: Application Of Sms To Soils and Its Effect On The Behaviomentioning
confidence: 99%
“…Because ruminants can digest the spent substrate with fungi, the spent substrate can be used for animal feed (Bisaria et al, 1997). It can also be used for animal bedding, soil conditioner, and fertilizer (Stewart et al, 1998), as well as for "biopulping" and "bioremediation" (Kirk et al, 1992a,b;Akhtar et al, 1993;Lamar et al, 1994;Eggen and Majcherczyk, 1998;Semple et al, 1998). Thus, the many uses of spent substrate allow total utilization of wood waste.…”
Section: Resultsmentioning
confidence: 99%
“…4. Semple et al (1998) found increased PAH removals when spent mushroom substrate was pre-enriched with PAHs. This was remarkable when compared with the 68% that remained in the CNT (no amendment) reactors.…”
Section: Time (Days)mentioning
confidence: 90%
“…Hogan et al (1989) investigated the composting of aliphatic and PAHs using mature compost at both 35 and 50 • C and found that, after 35 d, both temperatures provided similar removal of aliphatic hydrocarbons (e.g., octadecane) and PAHs (e.g., phenanthrene). Semple et al (1998) studied the extent of [U-14 C] benzene mineralization in spent mushroom compost after a 3-month enrichment period in the presence of benzene, toluene, ethylbenzene, and xylene (BTEX) compounds. They also found that when a temperature of 50 • C was maintained for 30 d, it resulted in more MOG degradation (70%) than that obtained at 23 • C over the same period of time.…”
Section: Introductionmentioning
confidence: 99%